A mereological argument for the non‐spatiotemporality of things in themselves. (19th August 2019) - Heide, Dai
Abstract: Kant's published arguments for the non‐spatiotemporality of things in themselves have not been well received. I argue that Kant has available to himself an argument for the non‐spatiotemporality of things in themselves that is premised upon a disparity between the compositional structure of the intelligible world and the structure of space and time. I argue that Kant was unwaveringly committed to the premises of this argument throughout his career and that he was aware of their idealistic implications. I also argue that this argument is consistent with Kant's restrictive mature epistemology. If my argument is successful, then even if Kant's published arguments for transcendental idealism fail, we need not regard his ambitious metaphysical project as a failure.